Experimental Investigation of a 10 MW Prototype Kaplan Turbine during Start-Up Operation - Soltani Dehkharqani, Arash; Engström, Fredrik; Aidanpää, Jan-Olov; Cervantes, Michel J. (Energies (Basel), 2019)
An increase in the start/stop cycles of hydraulic turbines due to the penetration of intermittent renewable energy sources is important. Hydraulic instabilities that occur in hydraulic turbines during start/stops may cause structural issues in the turbine components. High-stress fluctuations on the runner blades are expected during start-ups due to the unsteady pressure loading on the runner blades. This paper presents experiments performed on a 10 MW prototype Kaplan turbine at the Porjus Hydropower Center during a start-up cycle. Synchronized unsteady pressure and strain measurements on a runner blade and axial, bending (in two directions) and torsion strain measurements on the shaft were performed. In addition, the general parameters of the turbine (e.g., rotational speed, guide vane opening and runner blade angle) were acquired. Low-frequency fluctuations (0–15 Hz) were observed in the pressure data on the runner blade after opening the guide vanes from the completely closed position. A higher strain value was observed on the strain gauges installed on the runner blade near the hub (200–500 μ m / m ) compared to the ones near the shroud at the leading and trailing edge. The strain fluctuation level on the shaft decreased after loading the generator by further opening the guide vanes. Higher fluctuations were observed in the torsion strain compared to axial and bending strain. In addition, the torsion strain peak-to-peak value reached 12 times its corresponding value at 61% guide vane opening.